Agro-extraction in the Valley of the Urucuia River (state of Minas Gerais):: a study of pluriactivities and multifunctionality in the Cerrado biome - Bispo, Tayline Walverde; Diniz, Janaína Deane de Abreu Sá (Sustainability in Debate, 2014)
The Brazilian rural areas have undergone significant changes in recent decades, both in the production mode and in the lifestyle of its residents. In this context, some theoretical approaches have been proposed in order to better understand the dynamics of this new rural. Among these approaches, the concepts of pluriactivity and multifunctionality of agriculture provide demonstrations of knowledge and behaviors of rural households. The purpose of this article is to discuss applications of the concepts of pluriactivity and multifunctionality in the context of agroextractivism in the Cerrado biome. Data are described from field research carried out with agroextractivists of municipalities in the River Urucuia Valley, at Minas Gerais state. The results demonstrate and confirm the agroextractivism as pluriactivity and as a strategy of the families to stay in their property, with this activity also fulfilling multiple roles in the rural areas.